2017
DOI: 10.1002/jcp.26116
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant miRNA promoter methylation and EMT‐involving miRNAs in breast cancer metastasis: Diagnosis and therapeutic implications

Abstract: Breast cancer (BC) is the most prevalent cancer in women worldwide. Although extensive studies are ongoing concerning its intricate molecular mechanisms, development of novel therapies and more accurate diagnostic and prognostic approaches is still a challenge. Epithelial-mesenchymal transition (EMT) enables the invasion of metastatic cancer cells and has recently been highlighted in a Cancer Stem Cell (CSC) model of BC. Epigenetic events as well as miRNA expression are the master regulators of tumorigenesis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 142 publications
(291 reference statements)
2
66
0
Order By: Relevance
“…27 Regarding breast cancer, although extensive studies concerning its intricate molecular mechanisms are ongoing, development of novel therapies and more accurate diagnostic and prognostic approaches is still a challenge. 28 Herein, we identified that the expression of miR-708-3p was remarkably decreased in specimens from breast cancer patients with metastasis compared to specimens from patients with no metastasis. In addition, in vitro data showed that the expression level of miR-708-3p was negatively correlated with invasiveness in breast cancer cell lines, suggesting that miR-708-3p expression level may be a candidate biomarker for predicting breast cancer metastasis.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…27 Regarding breast cancer, although extensive studies concerning its intricate molecular mechanisms are ongoing, development of novel therapies and more accurate diagnostic and prognostic approaches is still a challenge. 28 Herein, we identified that the expression of miR-708-3p was remarkably decreased in specimens from breast cancer patients with metastasis compared to specimens from patients with no metastasis. In addition, in vitro data showed that the expression level of miR-708-3p was negatively correlated with invasiveness in breast cancer cell lines, suggesting that miR-708-3p expression level may be a candidate biomarker for predicting breast cancer metastasis.…”
Section: Discussionmentioning
confidence: 90%
“…In the present study, we also clarified the tumor inhibition mechanism of miR‐708‐3p in breast cancer. EMT occurs when epithelial cells lose their connections with their environment and achieve a mesenchymal phenotype, facilitating their entry into blood circulation and migration to distant locations . Studies show that breast cancer is an aggressive cancer with a high EMT‐associated metastatic ability .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is of utmost importance to explore the underlying molecular mechanisms and extract potential survival‐related signatures in the progression and prognosis of PAAD. Growing evidence has demonstrated that miRNAs are closely related to the onset and progression of many tumors . Moreover, miRNAs act as cancer biomarkers for early diagnosis, prognosis prediction, disease classification, and therapy efficacy .…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence has demonstrated that miRNAs are closely related to the onset and progression of many tumors. 23,24 Moreover, miRNAs act as cancer biomarkers for early diagnosis, prognosis prediction, disease classification, and therapy efficacy. 25,26 Thus, miRNA sequencing information was evaluated for patients with PAAD to systematically determine the F I G U R E 1 Differential expression of miRNAs between PAAD and adjacent normal samples.…”
Section: Discussionmentioning
confidence: 99%
“…A CpG island refers to a region with a cpG sequence density that is 10-20 times higher than the average density of the sequence, with >50% G + c content in a region >200 bases; ~50% of human genes contain cpG islands, for ~29,000 total cpG islands, which are normally located in the promoter region of the gene (8). in normal cells, cpG islands exist in a non-methylated state; however, high levels of methylation at cpG islands in housekeeping genes and tissue-specific genes are closely associated with inactivation of protein function and the Abnormal DNA methylation patterns in patients with infection-caused leukocytopenia based on methylation microarrays development of cancers and genetic diseases (9). Furthermore, methylation of cpG islands in some non-promoter regions, including intragenic, intergenic and downstream regions, may also cause pathological changes at the molecular level (10).…”
Section: Introductionmentioning
confidence: 99%